The Kish cypher the story of KLJN for unconditional security - Kish, Laszlo B. (World Scientific Pub., 2017)
This book clarifies the misinformation behind heated debates on the "Kish Cypher" (the popular but incorrect name for the Kirchhoff-Law-Johnson-Noise, KLJN, scheme), and debunks common misconceptions by using simple and clear-cut treatments to explain the protocol's working principle - an understanding that has eluded (even) several experts of computer science, quantum security, and electrical engineering. The work also explains how the scheme can provide the same (or higher) level of security as quantum communicators at a thousandth of the cost. The contents of this text address both layman and expert levels of understanding.